Short-term and long-term treatment with propafenone: determinants of arrhythmia suppression, persistence of efficacy, arrhythmogenesis, and side effects in patients with symptoms. Issue 6 (June 1992) - Zehender, M; Hohnloser, S; Geibel, A; Furtwängler, A; Olschewski, M; Meinertz, T; Just, H
Abstract : OBJECTIVE–To assess the clinical criteria predicting the short and long-term efficacy of propafenone, an agent with class IC antiarrhythmic activity and a broad pharmacological profile. DESIGNS–Prospective study of propafenone at doses of 450 to 900 mg/day during a six week dose titration period (including a placebo phase with two separate 24 Holter recordings). Responders to treatment were followed for one year. PATIENTS–One hundred patients with frequent ventricular arrhythmias (greater than 30 extrasystoles/h) of Lown class III and IVA/B and without evidence of myocardial infarction within the past six months. ANALYSIS–Multivariate regression analysis of spontaneous arrhythmia variability and of different clinical variables to determine the short and long-term efficacy and safety of propafenone. MEASUREMENTS AND MAIN RESULTS–Propafenone 450 mg/day was effective in 30/100 patients (30%), and at 600 mg/day another 14 responded. The efficacy of propafenone correlated with a low spontaneous arrhythmia variability and, as shown by multivariate analysis, with a lower patient age (p less than 0.05). When the dose was increased to 900 mg/day a further six (12%) patients responded. However, with increasing doses of propafenone, the one year probability of effective treatment decreased from 86% (450 mg/day) to 67% (600 mg/day) and to 44% (900 mg/day). After restudying the patients at three, six, and 12 months and after dose adjustment in 11/44 patients (25%), 31 patients (70%) remained responders. Loss of permanent antiarrhythmic efficacy was best predicted by the initial dose that achieved a response. No patient died suddenly or had arrhythmogenic effects during Holter monitoring. Side effects occurred in 36% of patients but these rarely limited long-term treatment. CONCLUSIONS–A younger age, low spontaneous arrhythmia variability, and particularly a low titration dose were the best predictors of the short and long term efficacy of propafenone. All other responders should have repeated Holter recordings during the first year of treatment.